Cover Image. (20th July 2018) - Lynch, Dustin T.; Leasure, Douglas R.; Magoulick, Daniel D.
Abstract : The cover image, by Dustin T. Lynch et al., is based on the Original Article The influence of drought on flow‐ecology relationships in Ozark Highland streams, DOI:10.1111/fwb.13089 . Image Credit: Dustin Lynch, Arkansas Natural Heritage Commission.